2013
DOI: 10.3390/su5030982
|View full text |Cite
|
Sign up to set email alerts
|

Swedish Upper Secondary School Students’ Conceptions of Negative Environmental Impact and Pricing

Abstract: This study explores relationships between upper secondary school students"

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 25 publications
(30 reference statements)
0
3
1
Order By: Relevance
“…These responses included both modes of transportation that reduce but do not eliminate emissions (35% of responses), such as using hybrid cars, and modes of transportation that eliminate emissions entirely (28% of responses), such as walking instead of driving to school (see Figure 1 1 ). Unlike results from Ignell, Davies, and Lundholm (2013), only two students referenced buying local as a way to reduce transportation-related emissions. Thirteen percent of students either did not answer or provided an irrelevant response.…”
Section: Conceptualizations Of Climate Change Mitigationcontrasting
confidence: 64%
“…These responses included both modes of transportation that reduce but do not eliminate emissions (35% of responses), such as using hybrid cars, and modes of transportation that eliminate emissions entirely (28% of responses), such as walking instead of driving to school (see Figure 1 1 ). Unlike results from Ignell, Davies, and Lundholm (2013), only two students referenced buying local as a way to reduce transportation-related emissions. Thirteen percent of students either did not answer or provided an irrelevant response.…”
Section: Conceptualizations Of Climate Change Mitigationcontrasting
confidence: 64%
“…Previous qualitative (eg Ignell, Davies, and Lundholm 2013) and quantitative (eg Sinatra et al 2012) research provides a basis for the design of items that may be used to gather data from samples that are large enough to offer some evidence of the changes highlighted in the research questions. This section describes and justifies the design, implementation and analysis of a survey used to gather evidence of change over a one year in the values, beliefs and norms of upper secondary school students in Sweden.…”
Section: Methodsmentioning
confidence: 99%
“…Vedung (1998) distinguished between policies acting through markets, regulation and information. Amadeo et al (2002) and Ignell, Davies, and Lundholm (2013) found differences among upper secondary students' beliefs about the efficacy of price changes and market interventions upon environmental problems. Based on these studies we devised items to capture evidence of belief in the efficacy of market forces (B3, B4, B6), education and information (B1, B2, B7); government intervention in markets through taxes and subsidies (B5, B8); government regulation (B9).…”
Section: Instrumentsmentioning
confidence: 99%
“…Wals (2015, p. 9) argues that '…despite the inevitable confusion, contestation and complexity that surround sustainability, there is quite a body of robust knowledge on each of these dimensions and, increasingly, how they are nested and how they influence each other. There is a lot we do know…' Thus, an increased focus on the interconnectedness of SD dimensions seems to be needed in the teaching and learning of sustainability issues (Kagawa 2007;Borg et al 2012;Ignell, Davies, and Lundholm 2013), especially if the transformative goals of ESD are to be reached.…”
Section: Holism and Interconnectedness In Esdmentioning
confidence: 99%